A new species of Polydiscia (Acari, Prostigmata, Tanaupodidae) with reference to its host: a new species of Deuterosminthurus (Collembola, Symphypleona, Bourletiellidae) - Baquero, Enrique; Moraza, Maria Lourdes; Jordana, Rafael (Zootaxa, 2003)
During the sampling campaign to describe the Iberian fauna of Collembola, an undescribed species of the family Bourletiellidae living on Genista hispanica L. was found with parasitic mites. The attached parasitic mites were identified as the larval instar of a new species of Polydiscia, a prostigmatid mite of the family Tanaupodidae Thor, 1935. The genus was previously cited in Austria. The Collembola, Deuterosminthurus bisetosus sp. nov, which was found in distant localities on the Iberian Peninsula, and Polydiscia deuterosminthurus sp. nov., are both here described. Both species were found together on Genista for three consecutive years. The abundant material obtained has allowed us to study both species with SEM (Scanning Electron Microscopy), and show characteristics in greater detail than has been possible with light microscopy.